Multi-scale processes drive benthic community structure in upwelling-affected coral reefs - Eidens, Corvin; Hauffe, Torsten; Bayraktarov, Elisa; Wild, Christian; Wilke, Thomas; Justus Liebig University Giessen (My University, 2015)
Environmental processes acting at multiple spatial scales control benthic community structures in coral reefs. However, the contribution of local factors (e.g., substrate availability and water clarity) vs. non-local oceanographic processes (e.g., upwelling events) in these highly complex systems is poorly understood. We therefore investigated the relative contribution of local and non-local environmental factors on the structure of benthic groups and specifically on coral assemblages in the upwelling-affected Tayrona National Natural Park (TNNP, Colombian Caribbean). Coral-dominated communities were monitored along with key environmental parameters at water current-exposed and -sheltered sites in four consecutive bays. Regression tree analyses revealed that environmental parameters explained 59% of the variation within the major benthic groups and 36.1% within coral assemblages. Findings also showed recurring patterns in community structures at sites with similar exposure across bays. We suggest that benthic community composition in TNNP is primarily driven by (1) wave exposure, followed by (2) temporal changes in nutrient availability governing the structure of benthic groups, and (3) local bay-specific differences controlling the zonation of benthic groups and coral assemblages. This study highlights the existence of complex hierarchical levels of local and non-local environmental factors acting on reef communities and stresses the importance of considering processes operating at multiple spatial scales in future studies on coral reef community structure and resilience.
Keywords: Colombian Caribbean; Tayrona National Natural Park; seasonal upwelling; wave exposure; environmental processes; ddc:570